Annual ring widths in the arctic-alpine dwarf-shrub species Betula Nana — Dataset from long-term alpine ecosystem research in Central Norway (LTAER-NO) - Albrecht, Eike Corina; Dobbert, Svenja; Keturka, Karolis; Kühnapfel, Mira; Francon, Loïc; Pape, Roland; Wundram, Dirk; Löffler, Jörg (ERDKUNDE, 2024)
Here we present a Data Paper with microscopically measured data on ring widths of the arctic-alpine dwarf shrub species Betula nana L. from Central Norway. We intend to continuously update the dataset in the future with further ring width measurements of this widespread shrub species.